A new ductile iron for mechanically and thermally strained rolls Part 2: material development varying Ni, Mo, Cr content using DoE. (2nd November 2021) - Duwe, Stephanie; Liepe, Martin; Schrumpf, Martin; Tonn, Babette; Bähr, Rüdiger
ABSTRACT: For manufacturing of steel wires, tubes and profiles in hot rolling mills, the toughest conditions occur in the front rolling stands where the mechanical load comes along with a constant change of hot rolling stock and cooling liquid. Conventional roll materials as pearlitic or acicular cast irons are not able to overcome these intense conditions because of their lack of ductility. A fine selection of alloying elements leads to a new material with a microstructure uniting bainite, austenite and martensite inducing high hardness and strength, without lacking elongation. For this purpose, a full-factorial design of experiments was created consisting of three alloying elements in two concentrations each. The alloys were cast, heat-treated and underwent extensive investigations on mechanical properties and microstructure. The results were analysed and implemented in mathematical models whose combination and optimisation led to the identification of the ideal alloy meeting the required strength, hardness and elongation.